Section Solutions for Chapter 9
Solutions to Exercise 9.1.3
9.1.3.2 To prove Proposition 9.1.2 requires strong induction, since the recursive relation calls on two previous terms. Thus, two base cases are required.
9.1.3.3 The formula from Proposition 9.1.2 gives
D5=5!((−1)00!+(−1)11!+(−1)22!+(−1)33!+(−1)44!+(−1)55!)=120(1−1+12−16+124−1120)=60−20+5−1=44.
9.1.3.4 The initial conditions are D1=0 and D2=1. The recursive relation Dn=(n−1)(Dn−1+Dn−2) for n≥3 gives D3=2(D2+D1)=2(1+0)=2. Now
D4=3(D3+D2)=3(2+1)=9,
and
D5=4(D4+D3)=4(9+2)=4(11)=44.
Solutions to Exercise 9.2.3
9.2.3.1 Proof. Base case: n=0. We have c0=1 (by definition) and 1>0, so c0>0.
Inductive step: We begin with the inductive hypothesis. We will require strong induction. Let k≥0 be arbitrary, and suppose that the inequality holds for every j with 0≤j≤k; that is, assume that for every such j, cj>0.
Now we want to deduce that ck+1>0. Using the recursive relation, we have
ck+1=k∑i=0cic(k+1)−i−1=k∑i=0cick−i.
Using the inductive hypothesis, we have cj>0 for every j such that 0≤j≤k. Putting these together gives that ck+1 is a sum of k+1 terms where each term has the form cick−i with 0≤i≤k. Since 0≤k−i≤k, we see that ci>0 and ck−i>0 so that cick−i>0. Hence
ck+1=k∑i=0cick−i>0.
This completes the proof of the inductive step.
By the Principle of Mathematical Induction, cn>0 for every n≥0. ◾Solutions to Exercise 9.3.6
9.3.6.1
B4=4∑k=1(3k−1)B4−k=(30)B3+(31)B2+(32)B1+(33)B0=5+3(2)+3(1)+1(1)=15.
9.3.6.3 If bi=(i+1)!/2 then the expanded exponential generating function for this sequence is
∞∑i=0bixii!=∞∑i=0(i+1)!xi2i!=∞∑i=0(i+1)xi/2.
This is
12∞∑i=0(i+1)xi=12(∞∑i=0(i+1)xi)=12(1−x)2.